High prevalence of multidrug resistant uropathogens: a recent audit of antimicrobial susceptibility testing from a tertiary care hospital in Bangladesh - Dasgupta, Chandrika; Rafi, Md. Abdur; Salam, Md. Abdus (Professional Medical Publications, 2020)
Objectives: Urinary tract infections due to multi drug resistant bacteria have been on the rise globally with serious implications for public health. The objective of this study was to explore the prevalence of multi drug resistant uropathogens and to correlate the urinary tract infections with some demographic and clinical characteristics of patients admitted in a tertiary care hospital in Bangladesh. Methods: A cross sectional prospective study was conducted at Shaheed Ziaur Rahman Medical College Hospital, Bogura, Bangladesh among clinically suspected urinary tract infection patients from January to December, 2018. Clean-catch midstream or catheter-catch urine samples were subjected to bacteriological culture using chromogenic agar media. Antimicrobial susceptibility testing of the isolates was done by KirbyBauer disk diffusion method following Clinical and Laboratory Standards Institute guidelines. Descriptive statistical methods were used for data analysis. Results: Culture yielded a total of 537 (42.8%) significant bacterial growths including 420 (78.2%) multi drug resistant uropathogens from 1255 urine samples. Escherichia coli was the most common isolate (61.6%) followed by Klebsiella spp. (22.5%), Pseudomonas spp. (7.8%), Staphylococcus aureus (5.4%) and Enterobacter spp. (2.6%) with multi drug resistance frequency of 77.6%, 71.9%, 90.5%, 86.2% and 92.9% respectively. There was female preponderance (M:F; 1:1.97; P=0.007) but insignificant differences between paediatric and adult population (43.65% vs. 42.57%) and also among different age groups. Diabetes, chronic renal failure, fever and supra-pubic pain had significant association as co-morbidities and presentations of urinary tract infections (P<0.05). Multi drug resistance ranged from 3.7 to 88.1% including moderate to high resistance found against commonly used antibiotics like ciprofloxacin, cephalosporin, azithromycin, aztreonam, cotrimoxazole and nalidixic acid (28.6 to 92.9%). Isolates showed 2.4 to 32.2% resistance to nitrofurantoin, amikacin, netilmicin and carbapenems except Pseudomonas spp. (66.7% resistance to nitrofurantoin) and Enterobacter spp. (28.6 to 42.9% resistance to carbapenems). Conclusion: There is very high prevalence of multi drug resistant uropathogens among hospitalized patients and emergence of carbapenem resistance is an alarming situation. Antibiotic stewardship program is highly recommended for hospitals to combat antimicrobial resistance.